2003
DOI: 10.1097/00042192-200310010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Hot flushes in a male population aged 55, 65, and 75 years, living in the community of Linköping, Sweden

Abstract: Hot flushes occur in one third of a population of noncastrated older men, approximately half of whom consider flushes as bothersome. Neither the mechanisms nor whether the symptoms would respond to testosterone supplementation is known. Androgen substitution to treat symptoms possibly related to a male climacteric is still controversial. Studies are needed to evaluate the needs for and the effects of androgen treatment on vasomotor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…The questionnaire was modified from previously used and validated questionnaires developed by us (29)(30)(31). To test comprehension, six women, 47-56 years old, were asked to answer the questionnaire in writing.…”
Section: Cross-sectional Study Performed In 2010mentioning
confidence: 99%
“…The questionnaire was modified from previously used and validated questionnaires developed by us (29)(30)(31). To test comprehension, six women, 47-56 years old, were asked to answer the questionnaire in writing.…”
Section: Cross-sectional Study Performed In 2010mentioning
confidence: 99%
“…We have previously reported that hot flushes, similar to those experienced by women during the climacteric period, are quite common in a population of ageing Swedish men, consisting of totally almost 1400 men, 55, 65 and 75 years old, and that the flushes cause significant discomfort for those men who report them [11].…”
Section: Partial Androgen Deficiency In Aging Males (Padam) or Androgmentioning
confidence: 94%
“…All that had to be done was to make a tick mark in one of a series of boxes. The questionnaire was slightly modified from a previously used and validated questionnaire developed by us [11,16].…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hot flushes occur in men with testicular insufficiency and in "normal aging men", but to a lesser extent [5,6]. Nearly 100% of reported flushes in women and men after castration therapy are objectively confirmed by increased blood-flow, skinconductance and/or skin-temperature [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%